2015 12th International Conference on the European Energy Market (EEM) 2015
DOI: 10.1109/eem.2015.7216715
|View full text |Cite
|
Sign up to set email alerts
|

Gap analysis of future energy grids

Abstract: Based on existing low and medium voltage grids from distribution system operators and future scenarios of PV and EV penetration, critical load scenarios which lead to violations of relevant KPIs are to be developed in the scope of PlanGridEV. In the course of the gap analysis the expected limits of DER hosting capacities were identified. The method for developing and simulating the different scenarios is following a state-of-the-art approach. Results for each power grid and scenario are addressing specific KPI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The estimated HC values of the rural networks are lower as compared to urban networks pertaining to the topological and electrical properties of the former [63] and due to the voltage rise issues at the end of long weak feeders [38]. HC of 239.7% with reference to the peak load of a Finnish LV balanced urban network for 0% MV change is higher than the HC of 198.1% of balanced rural network despite the similar geographical location of 61.9241° N [28].…”
Section: Estimated Hc Of Urban Suburban Rural Networkmentioning
confidence: 76%
See 4 more Smart Citations
“…The estimated HC values of the rural networks are lower as compared to urban networks pertaining to the topological and electrical properties of the former [63] and due to the voltage rise issues at the end of long weak feeders [38]. HC of 239.7% with reference to the peak load of a Finnish LV balanced urban network for 0% MV change is higher than the HC of 198.1% of balanced rural network despite the similar geographical location of 61.9241° N [28].…”
Section: Estimated Hc Of Urban Suburban Rural Networkmentioning
confidence: 76%
“…Two urban unbalanced LV networks in Kotte (6.8868 • N) and Perth (31.9505 • S) can accommodate the maximum HC values with respect to transformer rating as 40% and 31.9% in [72] and [39], respectively. The HC values without any mitigation means of three urban networks in the Northern hemisphere are found as 32 MWp, 522 kW and 4.8 MW (77%) in [88], [63] and [10], respectively. In [88], the authors investigated an uncontrolled and controlled PV deployment scenario for an urban network in Phapos, Cyprus (34.7720 • N) under two PF settings of unity and 0.95 and observed that performance indices start violating after 32 MWp.…”
Section: Estimated Hc Of Urban Suburban Rural Networkmentioning
confidence: 93%
See 3 more Smart Citations